Prospects of miRNA-Based Therapy for Pancreatic Cancer - Pai, Priya; Rachagani, Satyanarayana; Are, Chandrakanth; K. Batra, Surinder (Current Drug Targets, 2013)
Pancreatic cancer (PC) is the fourth leading cause of cancer related deaths in the U.S., with a less than 6% fiveyear survival rate. Treatment is confounded by advanced stage of disease at presentation, frequent metastasis to distant organs at the time of diagnosis and resistance to conventional chemotherapy. In addition, the molecular pathogenesis of the disease is unclear. The extensive study of miRNAs over the past several years has revealed that miRNAs are frequently de-regulated in pancreatic cancer and contribute to the pathogenesis and aggressiveness of the disease. Several studies have tackled the practical difficulties in the application of miRNAs as viable therapeutic and diagnostic tools. Given that a single miRNA can affect a myriad of cellular processes, successful targeting of miRNAs as therapeutic agents could likely yield dramatic results. The current review attempts to summarize the advances in the field and assesses the prospects for miRNA profiling and targeting in aiding PC treatment.
Keywords: MiRNA